2000
DOI: 10.1128/jb.182.14.3955-3964.2000
|View full text |Cite
|
Sign up to set email alerts
|

A New Two-Component Regulatory System Involved in Adhesion, Autolysis, and Extracellular Proteolytic Activity of Staphylococcus aureus

Abstract: A transposition mutant of Staphylococcus aureus was selected from the parent strain MT23142, a derivative of strain 8325. The site of transposition was near the 5 terminus of the gene arlS. ArlS exhibits strong similarities with histidine protein kinases. Sequence analysis suggested that arlS forms an operon with upstream gene arlR. The predicted product of arlR is a member of the OmpR-PhoB family of response regulators. The arlS mutant formed a biofilm on a polystyrene surface unlike the parent strain and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
199
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(207 citation statements)
references
References 57 publications
5
199
1
2
Order By: Relevance
“…Curiously, CesRK-like systems are absent in both S. aureus and B. subtilis, whereas in Enterococcus faecalis, the CesRKlike system CroRS has been shown to play a role in the intrinsic resistance to b-lactam antibiotics (Comenge et al, 2003;Hancock & Perego, 2004). In S. aureus, a LisRK-like system, ArlRS, has been shown to be involved in the control of autolysis, cell growth and virulence (Fournier et al, 2001;Fournier & Hooper, 2000;Liang et al, 2005); however in B. subtilis, LisRK-like systems are absent (Jordan et al, 2008). Collectively, these observations suggest that in L. monocytogenes, a regulatory network consisting of at least four TCSs is orchestrating the response to cell envelope stress.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, CesRK-like systems are absent in both S. aureus and B. subtilis, whereas in Enterococcus faecalis, the CesRKlike system CroRS has been shown to play a role in the intrinsic resistance to b-lactam antibiotics (Comenge et al, 2003;Hancock & Perego, 2004). In S. aureus, a LisRK-like system, ArlRS, has been shown to be involved in the control of autolysis, cell growth and virulence (Fournier et al, 2001;Fournier & Hooper, 2000;Liang et al, 2005); however in B. subtilis, LisRK-like systems are absent (Jordan et al, 2008). Collectively, these observations suggest that in L. monocytogenes, a regulatory network consisting of at least four TCSs is orchestrating the response to cell envelope stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although acid stress responses do not include increases in major virulence factors or biofilm formation, there were noteworthy changes in several global regulators that control the expression of virulence genes and drug efflux transporters (5), such as the SaeRS and ArlRS, two-component regulators, the Ser/Thr kinase PknB, and its phosphatase Stp1. These global regulators have been shown to be important in modulating virulence factor and drug transporter expression (9,11,22,23,26). Other regulators exhibit increased expression at pH 4.5, including the transcriptional regulator of the iron regulator Fur family (SACOL1541), the histidine kinases PhoP and KdpD, and the VraS protein of the cell wall stimulon response (10,14,16).…”
Section: Discussionmentioning
confidence: 99%
“…However, some known regulatory genes involved in capsule regulation, such as agr or mgr, were not identified, suggesting that the library is biased to some degree. Among the genes identified, we chose to focus on arl since this locus has been shown to be an important regulator affecting the expression of several virulence factors in S. aureus, including autolysin and various toxins (Fournier & Hooper, 2000;, but how it regulates capsule has not been studied. Our results showed that arl positively controlled the production of capsule.…”
Section: Discussionmentioning
confidence: 99%
“…The arlRS system has been shown to be involved in regulation of several virulence genes in S. aureus (Fournier & Hooper, 2000;). The two genes form an operon, and mutations in each gene have been shown to result in the same phenotype .…”
Section: Screening Of Tn551 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation